Chylomicron/chylomicron remnant turnover in humans: evidence for margination of chylomicrons and poor conversion of larger to smaller chylomicron remnants. - Karpe, F; Olivecrona, T; Hamsten, A; Hultin, M (1997)
The size of cholesterol-rich lipoprotein particles is a strong determinant of whether they may be deposited in the arterial wall and by this become potentially atherogenic. This study deals with the in vivo transformation of larger-sized chylomicrons and chylomicron remnants to smaller-sized remnants. Twelve healthy men aged 22 to 45 years were given a fatty meal to which retinyl palmitate (RP) had been added. Plasmapheresis was performed 4 1/2 h after meal intake to isolate approximately 400 ml plasma. The RP-rich plasma was re-injected to the subject 24 h later. The RP content was determined in whole plasma and in Svedberg flotation rate fractions (Sf) > 400, Sf 60-400 and Sf 20-60. A compartmental model was developed for the kinetic analysis. Lipoprotein fractions showed minimal signs of aggregation, thus arguing for well-preserved postprandial lipoproteins. Approximately a fourth [23% (4-68%)] of the RP-containing lipoproteins in the Sf > 400 pool was converted to smaller species (Sf 60-400). Conversion of material from the Sf 60-400 to the Sf 20-60 fraction could not be detected. In a second study a large bolus dose of a triglyceride emulsion (Intralipid) was injected to subjects shortly after the RP-labeled plasma to investigate the endothelial binding of the chylomicron/chylomicron remnants. RP material in the Sf > 400 fraction rapidly returned to plasma, arguing for margination of chylomicrons, whereas the corresponding effect was minimal in the Sf 60-400 and Sf 20-60 fractions. The formation of small chylomicron remnants from the larger chylomicron/chylomicron remnant species is limited and large chylomicron/chylomicron remnants are not evenly distributed in plasma, rather they show signs of being marginated to the vascular endothelium.